2019
DOI: 10.3389/fphys.2019.01258
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Running and High-Intensity Swimming Exercises Differentially Improve Energy Metabolism in Mice With Mild Spinal Muscular Atrophy

Abstract: Spinal Muscular Atrophy (SMA), an autosomal recessive neurodegenerative disease characterized by the loss of spinal-cord motor-neurons, is caused by mutations on Survival-of-Motor Neuron (SMN)-1 gene. The expression of SMN2, a SMN1 gene copy, partially compensates for SMN1 disruption due to exon-7 excision in 90% of transcripts subsequently explaining the strong clinical heterogeneity. Several alterations in energy metabolism, like glucose intolerance and hyperlipidemia, have been reported in SMA at both syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 75 publications
1
37
0
Order By: Relevance
“…In contrast, SMA type I patients have the increased work of breathing along with feeding and swallowing problems, contributing to reduced caloric intake and increased energy expenditure [ 50 , 51 ]. From a preclinical perspective, sedentary Taiwanese (Smn ∆7/∆7 ;SMN2 +/+ ) mice, a model of severe SMA, similarly have higher energy expenditure than control animals at 12 months of age [ 56 ].…”
Section: Baseline Anthropometric Data and Energy Expenditure Of Sma Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, SMA type I patients have the increased work of breathing along with feeding and swallowing problems, contributing to reduced caloric intake and increased energy expenditure [ 50 , 51 ]. From a preclinical perspective, sedentary Taiwanese (Smn ∆7/∆7 ;SMN2 +/+ ) mice, a model of severe SMA, similarly have higher energy expenditure than control animals at 12 months of age [ 56 ].…”
Section: Baseline Anthropometric Data and Energy Expenditure Of Sma Patientsmentioning
confidence: 99%
“…This was suggested to be compensatory to the high TG content in the Smn 2B/− livers in order to enhance clearance and restore homeostasis. Interestingly, a recent study showed that Taiwanese (Smn ∆7/∆7 ;SMN2 +/+ ) mice have a global shift in their respiratory exchange ratio, hence relying more heavily on β-oxidation [ 56 ]. The Smn 2B/− hepatic mitochondria produce more reactive oxygen species, leading to liver damage and functional deficit (protein production, hemostasis, complement, iron metabolism, insulin-like growth factor 1 (IGF1) pathway) [ 30 ].…”
Section: Intermediary Metabolism In Smamentioning
confidence: 99%
See 2 more Smart Citations
“…However, these trophic and SMN upregulation benefits were not observed in Type II patients performing arm cycling exercises [ 313 ]. Other studies evaluating the benefits of physical exercise in mild SMA model mice found improvements in glucose homeostasis, oxygen consumption, and muscle mitochondria function [ 314 ], especially when the exercise was high intensity. Chronic exercise in these mice improved muscle fatigue, neuromuscular excitability, and increased the resistance of muscles to damage [ 315 ].…”
Section: The Quest For Additional Sma Therapies: Smn-independent Tmentioning
confidence: 99%